Disease and Disorders of Freshwater Unionid Mussels: A Brief Overview of Recent Studies - Carella, Francesca; Villari, Grazia; Maio, Nicola; De Vico, Gionata (Frontiers in Physiology, 2016)
The use of aquatic invertebrates in biomedical research and as environmental sentinels has dramatically grown in recent decades, with an increased need in understanding of comparative pathology. The Unionids freshwater mussels are a group of worldwide distributed bivalves residing small ditches and ponds, lakes, canals and rivers, often used as animal test in eco-toxicological studies. Once one of the most abundant bivalve molluscs in ancient rivers around the world, now many of them are declining in many countries and consequently are nearly extinct in many areas. The causes of this decline are not fully understood but alteration and degradation of the freshwater habitat seemed to play a central role. To date, link causality to the observed losses during episode of mussel die-offs has been more difficult to establish, and disease and pathogen presence have been scarcely considered. In this article we provide a brief overview of unionids freshwater mussel conservation status, also describing reported diseases and pathogens and illustrating a few relatively well-documented studies.